Evaluation of thermal comfort and heat stress indices in different countries and regions – A Review. Issue 5 (September 2019) - Yasmeen, Sadia; Liu, Hong
Abstract: Energy efficiency, sustainability, productivity, thermal comfort, occupational health issues are emanating from rising global temperature associated with climate change. The prime purpose of this review is to focus on the present models to evaluate thermal comfort and heat stress level in various parts of the world in order to, identify the significant limitations in the development appropriate model. To assessed thermal comfort and heat stress a considerable number of models are already existing where about 40 models exist for only to determine heat stress itself. Existing comfort models are criticized for less metabolic rate, cloth insulation, not suitable for the outdoor diverse climate or for over or underestimation of the thermal concessions. On the other hand, to assessed heat stress WBGT-index is most widely used because of its simplicity. Several studies raised its limitations, whereas the PHS model is more appropriate but hard to understand for general people. For Thai people, HSI (Heat Stress Index) is best rather than others claimed by the authors. Thermal Work Limit (TWL) is suitable for both indoor and outdoor environments. Authors adopt the approaches to determine the region-based comfort and stress level through exploiting different models. For better evaluation models were improved through including or excluding new variables since the first development of thermal comfort indices. However, no unique model has developed afterward. Perfection and utilities of models depend on regional climatic behavior, which is apart from other relevant aspects. Therefore, further study should be necessary to establish a unique model or if not reasonable then focus on to obtain the accurate model for each climatic region.